Cross-cultural consumption : global markets, local realities - Howes, David, 1957- (Routledge, 1996)
What does an American refrigerator mean in the Solomon Islands?Cross-Cultural Consumption is a fascinating guide to the cultural implications of the globalization of a consumer society.